Detection of Human Movement Direction Using Optical Flow Analisys on Multiple Camera Angles - Wahyuni, Elvira Sukma; Iqbal, Zulfika; Farahiya, Dzata (Jurusan Teknik Elektro Universitas Andalas, 2021)
The active movement of children poses a safety risk in the absence of adult supervision. To reduce the risk of accidents in children, an automatic detection system for the direction of children's movements is crucially needed. In this study, detection of the direction of human movement based on image processing was carried out with the input of videos produce from 4 CCTV installed in each corner of the room. The system will detect the direction of object movement with classification of orientation, namely front, back, right and left. The detection method used in this research is Optical Flow. Optical Flow will calculate the value of the direction or orientation of the movement of an object. The orientation obtained is then accumulated with HOOF (Histogram Orientation of Optical Flow), where HOOF will collect the orientation of objects on the whole frame according to a 8-part Cartesian angle. The results of the orientation with Optical Flow will be compared with the direction of detection measured manually to determine whether the detection of movement direction using Optical Flow is running well. According to the results, it is known that the Optical Flow method has succeeded in detecting the direction of movement accurately based on different camera angles.Keywords :Â Image Processing, CCTV, Optical Flow, HOOF